2018
DOI: 10.1021/acs.jafc.8b03331
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Domain Truncation and Domain Insertion-Based Engineering of a Novel Thermostable Type I Pullulanase from Geobacillus thermocatenulatus

Abstract: A novel thermostable type I pullulanase gene ( pul ) from Geobacillus thermocatenulatus DSMZ730 was cloned. It has an open reading frame of 2154 bp encoding 718 amino acids. G. thermocatenulatus pullulanase (Pul) was found to be optimally active at pH 6.5 and 70 °C. It exhibited stable activity in the pH range of 5.5-7.0. Pul lacked three domains (CBM41 domain, X25 domain, and X45 domain) compared with the pullulanase from Bacillus acidopullulyticus ( 2WAN ). Different N-terminally domain truncated (730T) or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Notably, HvLD-Ser14Arg/His108Arg and HvLD-His108Arg were both also significantly more prone to substrate inhibition by pullulan (Table 1). Overall, the enzymatic properties of the mutants in the CBM21-like domain indicate an involvement in maintaining HvLD activity, as generally envisaged for a multidomain enzyme [56][57][58]. The larger losses of activity towards pullulan, amylopectin and -limit dextrin compared to the oligosaccharide substrate is in agreement with polysaccharides more readily perceiving changes at a remote area of the protein surface.…”
Section: Impact Of Remote Residues On the Catalytic Activity 321supporting
confidence: 62%
“…Notably, HvLD-Ser14Arg/His108Arg and HvLD-His108Arg were both also significantly more prone to substrate inhibition by pullulan (Table 1). Overall, the enzymatic properties of the mutants in the CBM21-like domain indicate an involvement in maintaining HvLD activity, as generally envisaged for a multidomain enzyme [56][57][58]. The larger losses of activity towards pullulan, amylopectin and -limit dextrin compared to the oligosaccharide substrate is in agreement with polysaccharides more readily perceiving changes at a remote area of the protein surface.…”
Section: Impact Of Remote Residues On the Catalytic Activity 321supporting
confidence: 62%
“…These results are in agreement with the reported type I pullulanases that hydrolyzed the 𝛼-1,6-glycosidic bonds of substrates. [45,46]…”
Section: Substrate Specificity Of the Purified Persipul1mentioning
confidence: 99%
“…Combination of enzymes and synergistic interactions between them could develop the bread characteristics and dough rheology. [10] Geobacillus thermocatenulatus DSMZ730 70 °C-pH 6.5 <50% activity after 120 min in 70 °C 7-8 [46] Bacillus methanolicus PB1 50 °C-pH 5.5 <20% activity after 120 min in 60 °C 5.5-6.5 [49] Anoxybacillus SK3-4 60 °C-pH 6 <10% activity after 60 min in 70 °C 5-7 [45] Paenibacillus polymyxa Nws-pp2 35 °C-pH 6 <10% activity after 50 min in 50 °C 5-6.5 [50] Exiguobacterium SH3 45 °C-pH 8.5 <10% activity after 90 min in 70 °C 5-11 [51] Shewanella arctica 35 °C-pH 6-7 <10% activity after 60 min in 40 °C 5-8 [52] Bacillus pseudofirmus 703 45 °C-pH 7-8 <20% activity after 10 min in 50 °C 6.5-8.5 [53] Metagenome-derived 40 °C-pH 6 -6-8 [18] Metagenome-derived (PersiPul1) 60 °C-pH 7 58.70% activity after 120 min in 80 °C 4-9 This study The same findings were reported after the usage of thermostable enzyme cocktail in the wheat bread. [9] 3.3.…”
Section: Synergistic Relationship Of the Persipul1and Persiamy2mentioning
confidence: 99%
“…SH3, [9] mesophilic Bacillus cereus, [10] thermophilic Geobacillus thermocatenulatus, and Anoxybacillus sp. WB42, [11,12] hyperthermophilic Pyrococcus yayanosii CH1, [13] etc. However, wild-type strains generally produce pullulanase at low level, leading to limited potential for industrial application.…”
Section: Introductionmentioning
confidence: 99%